Synthesis of nanocomposites reduced graphene oxide-silver nanoparticles prepared by hydrothermal technique using sodium borohydride as a reductor for photocatalytic degradation of Pb ions in aqueous solution - Ciptasari, Nurhayati Indah; Handayani, Murni; Kaharudin, Caesart Leonardo; Afkauni, Afif Akmal; Hatmanto, Adhi Dwi; Anshori, Isa; Maksum, Ahmad; Riastuti, Rini; Soedarsono, Johny Wahyuadi (Eastern-European Journal of Enterprise Technologies, 2022)
Heavy metals are pollutants that are harmful to living things and the environment can be degraded by microbes or understood by other living things so that they can cause health problems. One of the heavy metals that is often found in wastewater is lead. Lead is widely used in the manufacture of batteries, metal products such as ammunition, cable coatings, Polyvinyl Chloride (PVC) tubing, solder, chemicals and dyes This use causes humans to be exposed to large amounts of lead. One method to deal with lead pollution is to use photocatalysts. Photocatalysts react with heavy metals and reduce them so that the level of toxicity becomes lower than before through photocatalytic reactions. In this study, synthesis of reduced graphene oxide/silver nanoparticle nanoparticles was performed by facile hydrothermal methods for photocatalytic degradation of Pb ion. The characterization results indicate that the synthesis has been successfully carried out. The successful result of rGO/AgNPs nanocomposites synthesis was proved by several techniques such as X-ray diffraction analysis, Raman, UV-Vis spectroscopy, Scanning Electron Microscopy (SEM) and Energy Dispersive X-Ray analysis (EDX). This indicates the presence of these groups in the graphene oxide and rGO/AgNPs samples, respectively. The resulting rGO/AgNPs nanocomposite has an absorbance peak at a wavelength of 267 nm. The diffraction peaks for nanocomposites rGO/AgNPs and their Miller indices were 38.08° (111), 44.16° (200), 64.44° (220), and 77.44° (311). The Raman spectra of rGO/AgNPs exhibits D bands at 1334,13 with intensity of 630,60 cm−1 and G band at 1594,61 with intensity of 477,29 cm−1. The ID/IG ratio rGO/AgNPs-NaBH4 is ~1,32. Furthermore, the photocatalytic activity test results showed that the rGO/AgNPs nanocomposite was able to reduce Pb2+ to Pb with a maximum exposure time of 1.5 hours